1969
DOI: 10.1113/jphysiol.1969.sp008743
|View full text |Cite
|
Sign up to set email alerts
|

Renal receptors evoking a spinal vasometer reflex

Abstract: SUMMARY1. Certain afferent fibres in the renal nerves show an increased rate of discharge in response to small increases in renal vein pressure and to substantial increases of ureteral pressure. Such fibres enter the spinal cord largely through the upper lumbar dorsal roots.2. In spinal cats, stimuli exciting these afferent fibres evoke a reflex discharge in sympathetic nerves to the kidney and a fall in systemic arterial pressure. Change in flow or peripheral resistance, independent of arterial pressure, coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
0
1

Year Published

1971
1971
1992
1992

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 20 publications
4
30
0
1
Order By: Relevance
“…Arterial pressure has been reported to decrease during ARN electrical stimulation in the rat (Mahoney et al, 1981;Webb et al, 1982), whereas others have observed the opposite response (DiBona and Francisco, 1979;Hermansson et al, 1984). Similar conflicting evidence exists for other species (Aars and Akre, 1970;Ueda et al, 1967b;Beacham and Kunze, 1969;Calaresu et al, 1976Calaresu et al, , 1978. Such variations may, in part, reflect stimulation of mixed afferent popula-tions, since there is now clear evidence that the renal nerves contain a heterogeneous group of mechanoand chemoreceptor afferent fibers (Calaresu et al, 1978;Recordati et al, 1980).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Arterial pressure has been reported to decrease during ARN electrical stimulation in the rat (Mahoney et al, 1981;Webb et al, 1982), whereas others have observed the opposite response (DiBona and Francisco, 1979;Hermansson et al, 1984). Similar conflicting evidence exists for other species (Aars and Akre, 1970;Ueda et al, 1967b;Beacham and Kunze, 1969;Calaresu et al, 1976Calaresu et al, , 1978. Such variations may, in part, reflect stimulation of mixed afferent popula-tions, since there is now clear evidence that the renal nerves contain a heterogeneous group of mechanoand chemoreceptor afferent fibers (Calaresu et al, 1978;Recordati et al, 1980).…”
mentioning
confidence: 93%
“…Thus, although renal compression and raising renal venous or ureteral pressure have generally been reported to increase ARN activity (Beacham and Kunze, 1969;Niijima, 1971;Recordati et al, 1980;Kostreva et al, 1981;Kopp et al, 1984), no consistent effects of these stimuli on blood pressure or vascular resistance have emerged from previous studies. Both Pines (1960) and Niijima (1971) demonstrated a direct relationship between ARN activity and renal perfusion pressure in vascularly isolated kidneys in the cat and rabbit, respectively; however, cardiovascular parameters were not quantified in those studies.…”
mentioning
confidence: 96%
“…This suggests that a number of adaptive mechanisms may have been called into play. One possibility is the development of reflex control of blood pressure at a spinal level as shown in animal experiments (Beacham & Kunze, 1969;Andrews, Andrews & Orbach, 1971), and in spinal man (Guttmann & Whitteridge, 1947;Gilliatt, 1948;Gilliatt, Guttmann & Whitteridge, 1948;Corbett, Frankel & Harris, 1971a, b). Another possibility is that there may be a return of vascular tone (Sharpey-Schafer, 1961) which might be due to an increase in absolute levels of, or of sensitivity to, circu lating humoral agents (Johnson, Park & Frankel, 1971;Johnson & Park, 1973;Debarge, Christensen, Corbett, Eidelman, Frankel & Mathias, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Several animal models demonstrating this concept have stimulated this line of thought, although such pathways have not been discovered in man. Beachem and Kunze (1969) found that increasing renal BP in cats caused a sym pathetic reflex to the kidneys, subsequently lowering BP. Niijima (1971) demonstrated this same reflex in the renal blood vessels of rabbits, and Andrews et al (1971) described this phenomenon in mesenteric blood vessels of rabbits.…”
Section: Long-term Responses To Tilting and Standingmentioning
confidence: 99%